2002
DOI: 10.1097/00006676-200204000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Penetration of Meropenem and Cefepim into Pancreatic Tissue During the Course of Experimental Acute Pancreatitis

Abstract: Although both antibiotics penetrate into the necrotic tissue in sufficient therapeutic concentrations, penetration of meropenem is much better than cefepime. However, good tissue penetration may not solely indicate efficacy of that antibiotic. Therefore, further experimental and clinical studies are needed to determine the therapeutic and prognostic efficacy of these agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 27 publications
0
22
0
Order By: Relevance
“…Another potential advantage of meropenem over imipenem/cilastatin is that it can be given intravenously at a high rate without an increased risk of nausea or vomiting [29]. We currently provide evidence in a controlled experimental setting that meropenem can penetrate to pancreatic tissue in sufficient therapeutic concentrations, both in the early and late phases of ANP in rats [30], but the effectiveness of meropenem for prevention of secondary pancreatic infections in experimental AP is unknown. We have shown in this study that meropenem is effective for prevention of secondary pancreatic infections in experimental AP, both initiated early and late.…”
Section: Discussionmentioning
confidence: 99%
“…Another potential advantage of meropenem over imipenem/cilastatin is that it can be given intravenously at a high rate without an increased risk of nausea or vomiting [29]. We currently provide evidence in a controlled experimental setting that meropenem can penetrate to pancreatic tissue in sufficient therapeutic concentrations, both in the early and late phases of ANP in rats [30], but the effectiveness of meropenem for prevention of secondary pancreatic infections in experimental AP is unknown. We have shown in this study that meropenem is effective for prevention of secondary pancreatic infections in experimental AP, both initiated early and late.…”
Section: Discussionmentioning
confidence: 99%
“…The result for piperacillin agrees with the finding of no change in penetration into diseased tissue as reported previously (19). However, the current result for meropenem is in conflict with the work of Saglamkaya et al (17). They investigated animals both 6 h (disease characterized by edema) and 48 h (more necrotic tissue) following treatment with combined glycodexoxycholic acid infusion and intravenous cereulein to induce SAP.…”
mentioning
confidence: 72%
“…Perhaps this penetration would continue to decrease with time as the diseased tissue becomes less edematous. Several studies have shown that penetration differences (both increased and decreased) into diseased versus control tissue are more marked in the earlier and/or more edematous forms of acute pancreatitis (9,10,17), with evidence suggesting that this is on May 9, 2018 by guest http://aac.asm.org/ related to capillary pancreatic blood flow (9). The presence of more severe necrosis in Saglamkaya's work than in the present model may also have contributed to the higher penetration ratio at the 48-h time point.…”
mentioning
confidence: 99%
“…This is despite the fact that scientists have, for many decades, infused three forms of DCA into experimental animals to induce reproducible pancreatic injury. The three forms include the bile salt sodium deoxycholate, 7 – 9 the taurine conjugated bile salt (taurodeoxycholate), 10 and the glycine conjugated bile acid (glycodeoxycholic acid) 11 13 …”
Section: Discussionmentioning
confidence: 99%